Pengaruh Investment Opportunity Set Kebijakan Dividen Dan Financial Risk Terhadap Nilai Perusahaan Yang Dimoderasi Profitabilitas - Rosa Amalia Putri; Nera Marinda Machdar (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
Businesses must prepare themselves to cope with unpredictable economic changes. Every business must increase its value for long and short term business by considering current conditions in order to survive. This research aims to determine how business value is moderated in profitability by the set of investment opportunities, dividend policy, and financial risk. This study uses quantitative methods. Secondary data was used in this research. Manufacturing companies listed on the Indonesia Stock Exchange (BEI) were the subject of research for seven years, from 2015 to 2022. The research results show that investment opportunity sets, dividend policies and financial risks influence the firm value variable. The moderating variable profitability is able to strengthen the relationship between the variables Investment Opportunity Set, Dividend Policy and Financial Risk on Company Value.